Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1002/pro.4100
|View full text |Cite
|
Sign up to set email alerts
|

DNA‐binding domain as the minimal region driving RNA‐dependent liquid–liquid phase separation of androgen receptor

Abstract: Androgen receptor (AR) is a nuclear hormone receptor that regulates the transcription of genes involved in the development of testis, prostate and the nervous system. Misregulation of AR is a major driver of prostate cancer (PC). The primary agonist of full‐length AR is testosterone, whereas its splice variants, for example, AR‐v7 implicated in cancer may lack a ligand‐binding domain and are thus devoid of proper hormonal control. Recently, it was demonstrated that full‐length AR, but not AR‐v7, can undergo li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 54 publications
(60 reference statements)
0
20
0
Order By: Relevance
“…Recent reports linked the regions that contain AFs to the LLPS phenomenon [ 81 ]. In steroid NR family representatives, the androgen receptor (AR), the estrogen receptor (ER), and the glucocorticoid receptor (GR), LBD (AF2) seems essential for this process [ 81 , 82 , 83 ]. It was found that, in a cellular model of prostate cancer, only full-length AR could phase separate on its own [ 84 ], where its splice variant lacking LBD, AR-v7, did not undergo LLPS [ 83 ].…”
Section: Transcription Regulators and Liquid–liquid Phase Separationmentioning
confidence: 99%
See 4 more Smart Citations
“…Recent reports linked the regions that contain AFs to the LLPS phenomenon [ 81 ]. In steroid NR family representatives, the androgen receptor (AR), the estrogen receptor (ER), and the glucocorticoid receptor (GR), LBD (AF2) seems essential for this process [ 81 , 82 , 83 ]. It was found that, in a cellular model of prostate cancer, only full-length AR could phase separate on its own [ 84 ], where its splice variant lacking LBD, AR-v7, did not undergo LLPS [ 83 ].…”
Section: Transcription Regulators and Liquid–liquid Phase Separationmentioning
confidence: 99%
“…In steroid NR family representatives, the androgen receptor (AR), the estrogen receptor (ER), and the glucocorticoid receptor (GR), LBD (AF2) seems essential for this process [ 81 , 82 , 83 ]. It was found that, in a cellular model of prostate cancer, only full-length AR could phase separate on its own [ 84 ], where its splice variant lacking LBD, AR-v7, did not undergo LLPS [ 83 ]. This indicates that a cooperative interaction between NTD and LBD of AR is important for the phase separation of this receptor [ 83 ].…”
Section: Transcription Regulators and Liquid–liquid Phase Separationmentioning
confidence: 99%
See 3 more Smart Citations